(untitled) (Scientific journal of the Fergana State University, 2023)
This article deals with the problem in teaching architectural and construction terminology.As a result,the stages in the preparation of students are identified and characterized,which are aimed at developing the skills to stimulate the creative self-expression of students in the process of studying scientific and technical terminology.The analysis showed that, although terminological dictionaries are available in sufficient quantity, they cannot always be used for educational purposes.